Jesus and the future - Tiede, David Lenz (Understanding Jesus today, 1990)
Jesus' statements about the future provoked conflict among his own people and reprisal from the Romans; they remain controversial even today. Some readers of the New Testament study Jesus' words for specific predictions, searching for a road map to the future. Others transform Jesus' words into spiritual truths with little current relevance. This book challenges the reader to understand the historical realities that Jesus addressed. How did his message interpret Israel's hope in the midst of the ominous events of his time? How did his declaration of God's reign redefine the meaning of the present and the future of humanity and the world? Important passages concerning the future are examined in close connection to their real life contexts. Special attention is given to the book of Revelation.